The language of law and economics : a dictionary - Parisi, Francesco, 1962- (Cambridge : Cambridge University Press, 2013)
'From a historical perspective,'law and economics' was one of the most influential developments in legal scholarship in the twentieth century; it remains today one of the dominant perspectives on the law, generating a tremendous quantity of new research and discussion. Unfortunately, the rewards of applying the analytical methods of one highly technical field to the historically layered substance of another has resulted in considerable overhead, requiring fluency in both the language of economics and the language of the law. Further complicating matters, law and economics has sometimes developed independently, creating new terms, while recasting others from their original economic or legal meanings. In this dictionary of law and economics, Francesco Parisi provides a comprehensive and concise guide to the language and key concepts underlying this fecund interdisciplinary tradition. The first reference work of its kind, it will prove to be an invaluable resource for professionals, students and scholars'--
Machine generated contents note: Introduction; Dictionary of law and economics; Bibliography; Index by subject; Index by authors
Includes bibliographical references (pages 326-346) and indexes.
Keywords: Law -- Economic aspects -- Dictionaries; Law and economics -- Dictionaries